Dialogues between teaching knowledge and the training of the licensed in geography: contributions from pibid - Paiva Medeiros Nonato, Raiany Priscila; do Nascimento, Maria Juliana; de Assis, Mariana Pricilia; Moreira da Silva, Cicero Nilton (Revista Ensino de Geografia (Recife), 2021)
In this article, the contribution of the Institutional Teaching Initiation Scholarship Program (PIBID) to the teaching of Geography is analyzed. It is based on a qualitative approach, combining with bibliographic type research and the use of language, it presents analyzes based on Content Analysis (AC). It is verified, through constructed data, that the PIBID Geography Subproject has promoted the improvement of the education of the graduate in Geography, through the protagonist of the teaching action, in different ways: of prolonged experience in the school environment; from the experience with the construction of didactic-pedagogical materials in schools, from the construction and development of projects, as well as in the course of socializing these experiences in the academic and school environments.